Aggressive bougie dilatation and intralesional steroids is effective in refractory benign esophageal strictures secondary to corrosive ingestion. Issue 8 (6th November 2015) - Nijhawan, S.; Udawat, H. P.; Nagar, P.
Summary: Endoscopic dilatation of corrosive esophageal strictures is effective, but some patients are refractory to it and require long‐term repeated dilatations. The present study was carried out to analyze whether rigorous schedule of endoscopic bougie dilatation along with intralesional injection of triamcinolone in patients refractory to endoscopic dilatation alone could decrease the number and frequency of endoscopic dilatations. The inclusion criterion for this prospective study was patients with refractory corrosive esophageal stricture of any age group. Refractory benign esophageal stricture is defined as an anatomic fibrotic esophageal restriction with inability to achieve dilatation of ≥14 mm or to maintain dilatation for 4 weeks once ≥14 mm diameter is achieved. The patients were followed up prospectively for 1 year. Patients with refractory strictures were subjected to weekly bougie dilatation (Savary‐Gilliard) of the strictures along with injections of intralesional triamcinolone (40 mg/mL, 1 mL diluted in 1 mL of saline, 0.5 mL injected per quadrant of stricture) for consecutive 5 weeks, referred to as rigorous schedule. Further dilatation was done on an 'on‐demand' basis. Eleven patients were enrolled for the study. Dysphagia score improved from pre‐intervention score of 3.54 ± 0.52 to 0.45 ± 0.52 post‐intervention ( P < 0.001). The maximum dilatation achieved pre‐intervention was 9.90+1.04 mm Savary‐Gilliard and post‐intervention significantly improved to 14.7 + 0.7 mm Savary‐Gilliard ( P < 0.001). The periodic dilatation index defined as number of dilatations per month also significantly improved from pre‐intervention score of 2.54 ± 1.06 to post‐intervention score of 0.19 + 0.13 ( P < 0.001). No adverse effects were reported by the patients. Rigorous weekly schedule of bougie dilatation and intralesional triamcinolone in combination is safe and effective in achieving significant dilatation, reducing the frequency dilatations, maintaining dilatation and improving dysphagia till 1 year of follow‐up.